Decontamination of heavy metal laden sewage sludge with simultaneous solids reduction using thermophilic sulfur and ferrous oxidizing species. (1st February 2016) - Mehrotra, A.; Kundu, K.; Sreekrishnan, T.R.
Abstract: A possibility of using simultaneous sewage sludge digestion and metal leaching (SSDML) process at the thermophilic temperature to remove heavy metals and suspended solids from sewage sludge is explored in this study. Though thermophilic sludge digestion efficiently produces a stable sludge, its inability to remove heavy metals requires it to be used in tandem with another process like bioleaching for metal reduction. Previously, different temperature optima were known for the heterotrophs (thermophilic) responsible for the sludge digestion and the autotrophs involved in bioleaching (mesophilic), because of which the metal concentration was brought down separately in a different reactor. In our study, SSDML process was carried out at 50 °C (thermophilic) by using ferrous sulfate (batch-1) and sulfur (batch-2) as the energy source in two reactors. The concentration of volatile suspended solids reduced by >40% in both batches, while that of heavy metals zinc, copper, chromium, cadmium and nickel decreased by >50% in both batch-1 and batch-2. Lead got leached out only in batch-1. Using 16S rRNA gene-based PCR-denaturing gradient gel electrophoresis analysis, Alicyclobacillus tolerans was found to be the microorganism responsible for lowering the pH in both the reactors at thermophilic temperature. The indicator organism count was also below the maximum permissible limit making sludge suitable for agricultural use. Our results indicate that SSDML at thermophilic temperature can be effectively used for reduction of heavy metals and suspended solids from sewage sludge. Graphical abstract: Highlights: Simultaneous sewage sludge digestion and metal leaching was carried out at thermophilic temperature (50 °C). Sludge was stabilized with a reduction in heavy metals load. Pathogens were below the detection limit in the treated sludge. Microbial community analysis showed Alicyclobacillus tolerans as the dominant microorganism for carrying out the bioleaching.